DETERMINANTS OF COMMUNITY PARTICIPATION IN ORADEA - SAVEANU TOMINA GABRIELA (Annals of the University of Oradea: Economic Science, 2011)
The present paper is part of the research of the PhD thesis made by the author, having the title: Community Participation in Oradea, registered at the University of Oradea - Faculty of Social and Human Sciences. The general objectives of the paper are the explanation of different types of citizens involvement in the life of their community, the investigation of the existing relationships between different forms of participation, the interpretation of the effects different forms of participation have on the studied communities and the identification of relevant mechanism for the stimulation social involvement. The citizens' political and civil participation, social responsibility, community spirit, civic activism together with other concepts from the civil society's rhetoric entered the agenda of public debates together with the intensifying efforts for adhering to the European Community, being the subject of numerous studies conducted in this field. The need for a strong civic society, with interested and involved citizens in the life of the community which they belong to, for social and economical development belong to the same discourse of the strong democratic society, being challenged in the literature, starting with Tocqueville, Almond and Verba, to Putnam and many others. In parallel to the civil society's rhetoric and the analysis coming from this direction, are the studies and theories of community development, which on one side are based on development policies, regulations, institutional framework of development, but contain also aspects of citizens' involvement in evaluating the community problems, the decision making processes and in the actual implementation of solutions. Moreover the aspects of network belonging and social trust which are reflected in the concept of social capital are sources both for participation as well for economic and social development. The present paper reflects the analysis of the determinant factors which can increase the engagement rates in the community life of the Romanians, engagement which is relevant on the production of different types of collective goods. The analysis is based on data obtained with the CEEX research, coordinated by Adrian Hatos, "Leaders, Participants and Viewers. Determinants of community participation in the urban Romania". The tested hypotheses in the research part, based on the results of different studies and theoretic approaches, derive from the general question of the paper: which are the factors that determine the community participation of the people living in Oradea. Thus, the participation variation is verified by: gender, age, social status, social capital, civic competence, leadership experience, participation opportunities. The main results suggest that community participation is explained by civic competence, well-being, bridging social capital, gender and age.